EVALUASI STRATEGI PENGGUNAAN JENIS PESAWAT PT SRIWIJAYA AIR DALAM MENGHADAPI PERSAINGAN - , Charles An ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In the recent tight airlines competition, the term of effective and efficient are commonly used by the airlines. This is due to by implementing these two terms, then they will have an impact on organization and company, particularly on airlines company. Many changes should be carried out specifically on airlines company management that still face inefficiency and ineffectively related to cost. As a business organization, airlines company should make efforts to encounter the fuel (avtur) price increase issue since 2004 and in present time, political issue in Middle East and North Africa region. PT. Sriwijaya Air, as a one of the airlines company or air service transportation provider, should decide precisely based on already exists initiatives to improve revenue and profit and make them sustainable regarding to avtur price increase. The avtur price is a major component that directly has an impact to operational cost and tariff. This becomes increasingly important because political issue on Middle East is a critical one. PT. Sriwijaya Air should start its initiatives to decide type of aircraft that economical and can compete with competitor in airlines industry. They should also implement right strategy in accordance with target market or market segment to determine tariff for obtaining high yield.